Bronchoalveolar lavage as a tool for assessing potential occupational exposure: a retrospective study (International Journal of Occupational Safety and Health, 2026)
Introduction: Bronchoalveolar lavage (BAL) is a fundamental diagnostic procedure for evaluating diffuse parenchymal lung diseases (DPLDs). However, its diagnostic precision is critically dependent on the integration of a detailed occupational history. Occupational exposures are frequently overlooked in clinical practice, leading to potential misdiagnosis.Methods: We conducted a retrospective analysis of 210 BAL samples from 207 patients over one calendar year at a tertiary referral hospital in Attica, Greece. Data regarding demographics, smoking status, and occupational history (classified via ISCO-08) were correlated with BAL cytology using descriptive statistics, χ² tests, t-tests, and one-way ANOVA with post-hoc comparisons. Missing data were supplemented through extensive record review and patient interviews.Results: Occupational history was absent in 79.5% of initial clinician referrals. Upon data completion, 23.3% of patients were identified as active workers. Workers in the agricultural and forestry sector (ISCO-08 Group 6) showed significantly higher total BAL cell counts (P = 0.025) and specific cytological patterns, including increased macrophages and mast cells. While smoking significantly altered differential counts, it did not influence the total cell count.Conclusion: Specific BAL profiles are associated with certain occupational groups, yet a significant gap in history-taking persists. Systematic occupational assessment is mandatory to improve the diagnostic utility of BAL in respiratory medicine. These findings suggest that BAL can serve as a valuable 'sentinel tool' for occupational surveillance in respiratory medicine.